Determination of Vitamin C in Small Volumes of Blood by HPLC/EC: Determination of vitamin C in blood - G. Watson, David; Lotfollahzadeh, Samad; Mokhber Dezfoulib, Mohammad Reza; Hadjiakhoondic, Abbas (Iranian Journal of Pharmaceutical Sciences, 2005)
A sensitive procedure for determining total vitamin C (ascorbic acid + dehydrate ascorbic Acid) in a blood drop from a finger prick, before and after the administration of a vitamin C tablet is described. Analysis was carried out by high performance liquid chromatography with electrochemical detection (HPLC/EC). Measurements were taken one hour, two hours and six hours after the administration of a 500 mg vitamin C tablet. D-Isoascorbic acid was used as the internal standard and analysis was carried out using two C-18 columns connected in series and a phosphate buffer mobile phase. Dehydroascorbic acid in the samples was converted to ascorbic acid by incubation with DL-homocysteine for 30 minutes. The level of vitamin C in blood reached a maximum concentration after two hours.